Perencanaan Embung Sebagai Upaya Pengendalian Banjir di Kecamatan Cikampek Kabupaten Karawang - Sin Sin Husnul Rizal; Sulwan Permana (Institut Teknologi Garut, 2026)
The Cigelam Sub-watershed is located in the Cikarokrok watershed area in Cikampek Sub-district, Karawang Regency. Seasonal flooding is a concern, a fear for the local community. Hydrological analysis and reservoir design planning are emergency responses to natural disaster flooding events. The purpose of the research conducted this time was to calculate the design flood discharge of the Cigelam river, and flood control in Cikampek District. This research uses the Snyder Hydrograph method by designing the design rainfall and then testing the Chi Square distribution and the Smirnov - Kolmogorov Test. The design of the reservoir becomes the final stage of the research after the design flood discharge is obtained. The calculation obtained a maximum discharge of 1.266 m3/det and a planned flood discharge = 318.272 m3/det. The result of the calculation is the amount of design flood discharge with a 2-year return period (Q2) of the Cigelam river of 104.47 m3/det, (Q5) =161.71 m3/det, (Q10) = 199.61 m3/det, (Q25) = 247.49 m3/det, (Q50) 283.013 m3/det, (Q100) = 318.27 m3/det. The effective storage volume of the Cigelam river reservoir is 153,686.05 m3. The maximum amount of flood discharge that enters the reservoir when the Cigelam river reservoir is planned is 17.79 m3/det. This research contributes to the management of Cigelam river water resources in Cikampek District.